Case report and literature review: plexiform schwannoma in the penile and inguinal region in a child - Qi, Xiaoying; Tan, Yifei; Feng, Yanru; Ma, Dan; Wang, Ling; Pang, Houqing (Frontiers in Oncology, 2024)
Penile schwannoma is an uncommonly seen peripheral nerve tumor, of which penile plexiform schwannomas (PS) is extremely rare that has only been reported in several adults. We present a case of penile PS with a similar lesion in inguinal region in a 9-year-old child, which appeared as painless masses and rapidly growing within one year. Penile ultrasonography suggested well-defined lesions with limited vascularity. Both masses presented with low-to-intermediated signal intensity and no definite enhancement in computed tomography. The lesions were completely resected with minimal intraoperative bleeding, and a diagnose of benign PS was confirmed based on H&E staining and positive S-100 expression in immunohistochemistry. There was no evidence of tumor recurrence or metastasis after 6 months of follow-up. Only 6 cases of penile schwannoma in children were recorded, of which 5 were malignant, and none was PS. The malignancy rate of penile schwannoma in children may be overestimated due to delayed diagnose of benign ones. A rapidly growing penile mass with a suspected metastatic lesion in inguinal region could be easily misdiagnosed as malignant. This case report and literature review is expected to assist clinicians in getting a comprehensive understanding of children penile schwannomas and choosing the best management strategy when faced with this rare condition.